1992
DOI: 10.1002/gps.930070903
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological differentiation of Alzheimer's disease from vascular dementia

Abstract: SUMMARYThe purpose of this study was to determine whether cognitive test performances alone could distinguish patients with probable Alzheimer's disease from those with probable vascular dementia. Sixty-eight outpatients with clinical diagnoses of either Alzheimer's disease or vascular dementia were administered a brief battery of neuropsychological tests. Scores from the Boston Naming Test and the Hopkins Verbal Learning Test were identified as most discriminating of the groups. Seventy-seven per cent of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 32 publications
4
35
1
3
Order By: Relevance
“…A closer look at the other studies [2,5,9,11] revealed that our controls had a slightly lower performance than theirs. This may be explained by their very rigorous health screening of controls [2,5] or the lack of control for age, education, gender [2] and depression [2,11]. These factors may have overestimated the normal performance of elderly subjects in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A closer look at the other studies [2,5,9,11] revealed that our controls had a slightly lower performance than theirs. This may be explained by their very rigorous health screening of controls [2,5] or the lack of control for age, education, gender [2] and depression [2,11]. These factors may have overestimated the normal performance of elderly subjects in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…A later study reported 96% sensitivity and 80% specificity for mild dementia (MMSE 118) [9]. In studies of its discriminative capacity for different types of dementia, the HVLT was found to have a moderate (64% [10] to 77% [11]) correct classification rate for AD and vascular dementia (VaD).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ao contrário, relatos de melhor desempenho dos pacientes com DV na expressão linguística também são encontrados na literatura (Villardita, 1993;Powell et al, 1988;Barr et al, 1992;Chapman, 1997). Outros estudos ainda, não encontraram diferenças significativas entre o desempenho linguístico de pacientes com DV e pacientes com DA (Bentham et al, 1997;Vuorinen et al, 2000).…”
Section: Estudos Neuropsicológicos Comparativos Entre Demência Vasculunclassified